2018
DOI: 10.1002/mop.30981
|View full text |Cite
|
Sign up to set email alerts
|

Multiband reconfigurable Bowtie slot antenna using switchable slot extensions for WiFi, WiMAX, and WLAN applications

Abstract: In this letter, a compact multi‐band reconfigurable CPW fed bowtie slot antenna is presented and these performances are discussed. The known properties of the bowtie antenna, namely a high gain and a fairly large bandwidth have been used in order to design a reconfigurable multiband antenna which makes it possible to switch between a single band (initial mode) and dual band or triple band modes, making it more agile in frequency. The proposed approach is based on the integration of two pairs of slots on the tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…Various reconfigurable antennas with distinct switching have been tested; they include a novel switchable multiband frequency reconfigurable microstrip square slot antenna [10], and a novel bowtie frequency reconfigurable antenna [11]. A reconfigurable multiband bowtie slot antenna employs switchable pairs of slots [12]. A simple multiband reconfigurable antenna with dual pairs of PIN diodes [13] and a compact quad-band reconfigurable monopole antenna [14] have also been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Various reconfigurable antennas with distinct switching have been tested; they include a novel switchable multiband frequency reconfigurable microstrip square slot antenna [10], and a novel bowtie frequency reconfigurable antenna [11]. A reconfigurable multiband bowtie slot antenna employs switchable pairs of slots [12]. A simple multiband reconfigurable antenna with dual pairs of PIN diodes [13] and a compact quad-band reconfigurable monopole antenna [14] have also been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…From this table, it is clear that the proposed antenna has the highest gain compared to those antennas in [12,13,15,16], and lower than that of [14]. However, the proposed antenna has a smaller size.…”
Section: Comparison With Some Existing Antennasmentioning
confidence: 91%
“…Jalilvand et al presented and investigated antenna based on a new 3D microwave tomography approach [27]. Mansoul et al presented a compact antenna with 8 × 3 cm 2 space and obtained the enhanced peak gain performance of 4.5-5.8 dBi [28]. Wu et al [29] reported work on the slotted bowtie antenna with compact size (6 × 10 cm 2 ) and achieved a fair gain performance of 3.75 dBi, 3.56 dBi, and 3.93 dBi.…”
Section: Introductionmentioning
confidence: 99%
“…e authors in [35] investigated the antenna array with complex methodology and obtained the gain higher than 8 dBi. It is worthy noted that the results analyzed and explained in [25][26][27][28][29][30][31] the researchers have not paid attention to the radiation efficiency of the antennas; also, the suggested methods were complex. However, the proposed antenna presented in this paper employed an alternative method that outperforms the maximum gain, radiation efficiency, and compact dimensions in comparison with most of the previously reported work.…”
Section: Introductionmentioning
confidence: 99%